Rice Starch Particle Interactions at Air/Aqueous Interfaces—Effect of Particle Hydrophobicity and Solution Ionic Strength - McNamee, Cathy E.; Sato, Yu; Wiege, Berthold; Furikado, Ippei; Marefati, Ali; Nylander, Tommy; Kappl, Michael; Rayner, Marilyn (Frontiers in Chemistry, 2018)
Starch particles modified by esterification with dicarboxylic acids to give octenyl succinic anhydride (OSA) starch is an approved food additive that can be used to stabilize oil in water emulsions used in foods and drinks. However, the effects of the OSA modification of the starch particle on the interfacial interactions are not fully understood. Here, we directly measured the packing of films of rice starch granules, i.e. the natural particle found inside the plant, at air/aqueous interfaces and the interaction forces in that system as a function of the particle hydrophobicity and ionic strength, in order to gain insight on how starch particles can stabilize emulsions. This was achieved by using a combined Langmuir trough and optical microscope system, and the Monolayer Interaction Particle Apparatus. Native rice starch particles were seen to form large aggregates at air/water interfaces, causing films with large voids to be formed at the interface. The OSA modification of the rice starches particles decreased this aggregation. Increasing the degree of modification improved the particle packing within the film of particles at the air/water interface, due to the introduction of inter-particle electrostatic interactions within the film. The introduction of salt to the water phase caused the particles to aggregate and form holes within the film, due to the screening of the charged groups on the starch particles by the salt. The presence of these holes in the film decreased the stiffness of the films. The effect of the OSA modification was concluded to decrease the aggregation of the particles at an air/water interface. The presence of salts, however, caused the particles to aggregate, thereby reducing the strength of the interfacial film.